PENERAPAN MODEL PEMBELAJARAN KOOPERATIF QUICK ON THE DRAW UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN KOLOID KELAS XI SMA NEGERI 1 TANAH MERAH KABUPATEN INDRAGIRI HILIR - Nilda Desmariza Nilda Desmariza; Rasmiwetti ' '; Maria Erna Maria Erna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The purpose of this research to increase student achievement on the subject of koloid in class XI SMA Negeri 1 Tanah Merah and to know percentage student achievement on the subject of koloid in class XI SMA Negeri 1 Tanah Merah . Form of research is experiment research with pretest-posttest design. The sample consisted of two classes. Experiment class was given implementing model cooperative learning Quick on the draw, while the control class used discussion information methods. The t-test is used for data analysis technique. Based on the final results of data processing using t-test formula with dk=61 and ɑ=0,05 obtained tarithmetic>ttable (2.83>1.68) means that the application of model cooperative learning Quick on the draw can improve student achievement on the subject of koloid in class XI SMA Negeri 1 Tanah Merah, with an increasing percentage of 11,61 %.Keywords : Quick on the draw, Learning Achievement, and Koloid